Effects of Urban Expansion and Dispossession on Household Food Security and Sustainable Livelihood of Displaced Preurban Farmers in Addis Ababa, Ethiopia - Gnamura , Kejela; Antwi, Michael; Abenet, Belete (Studia Ecologiae et Bioethicae, 2025)
Urban expansion in Addis Ababa presents significant challenges, particularly for peri-urban farming communities facing displacement. This study investigates the critical link between land grabs, forced displacement, inadequate compensation, and food insecurity in households among displaced preurban farmers in the peripheries of Addis Ababa. Using a mixed-method approach, including the household food security index and the binary logistic regression model, we compare the food security status of displaced and nondisplaced households in the Lemmi Kura subcities of Addis Ababa and the Kura Jidda subcities of Sheger City. The findings demonstrate a substantial decrease in food security among displaced households, with significant reductions in food availability, access, utilisation, and stability. The logistic regression model reveals that displacement status, along with factors such as social capital and land security, significantly influences household food security. Specifically, displaced households had a 93.4% lower likelihood of food security compared to non-displaced households. Furthermore, the logistic regression model revealed that the displacement status (displaced = 1 and non-displaced = 0) had a negative coefficient (-2.717), indicating an inverse relationship between the displacement status and food security. Households that have experienced displacement are significantly less likely to have food security compared to nondisplaced households (p < 0.001). The results underscore the discrepancies between Ethiopia's urbanisation rhetoric and the realities faced by displaced farmers, advocating for policy reforms that align urban growth with food sovereignty and agrarian justice. By comprehensively addressing these issues, policy makers and urban planners can work toward more inclusive and sustainable urban development that preserves food security and livelihoods for vulnerable peri-urban communities.